2021
DOI: 10.1002/adfm.202101284
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired Tumor Calcification Enables Early Detection and Elimination of Lung Cancer

Abstract: Precise diagnosis of cancer in an early stage and treatments with a reliable response, high selectivity, and negligible side effects is urgently needed. However, current cancer management involves low‐resolution metrics and delayed visual confirmation of tumor foci in imaging findings, and the toxicity of chemo‐ and radiotherapy unavoidably damages normal tissue and disrupts the immune balance of cancer patients. Here, a polypeptide is synthesized that preferentially targets lung cancer cells rather than norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 35 publications
0
23
0
Order By: Relevance
“…The tumor calcification affects the metabolism and proliferation of tumor cells, induces the metabolic disorder and dysfunction of tumor cells, and eventually leads to cell death. These calcification phenomena inspire scholars to explore and study whether Ca 2+ enrichment in tumor foci can promote the development of tumor calcification, which has potential clinical significance for the early identification of solid tumors [ 107 , 187 ]. In fact, recent researches have cleared that tumor calcification is a long, slow process of calcium mineral deposition in focal tissues caused by abnormal local accumulation of Ca 2+ in the tumor microenvironment, which is considered to be the result of calcium overload [ 188 , 189 ].…”
Section: Calcium-based Nanomaterials For Cancer Diagnosis and Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…The tumor calcification affects the metabolism and proliferation of tumor cells, induces the metabolic disorder and dysfunction of tumor cells, and eventually leads to cell death. These calcification phenomena inspire scholars to explore and study whether Ca 2+ enrichment in tumor foci can promote the development of tumor calcification, which has potential clinical significance for the early identification of solid tumors [ 107 , 187 ]. In fact, recent researches have cleared that tumor calcification is a long, slow process of calcium mineral deposition in focal tissues caused by abnormal local accumulation of Ca 2+ in the tumor microenvironment, which is considered to be the result of calcium overload [ 188 , 189 ].…”
Section: Calcium-based Nanomaterials For Cancer Diagnosis and Therapymentioning
confidence: 99%
“…It has been clinically proved that tumor calcification can be considered a benign prognostic indicator after therapy [ 107 , 187 ]. Therefore, based on the CT imaging to tumor calcification, the researchers developed a series of combination diagnoses and therapy.…”
Section: Calcium-based Nanomaterials For Cancer Diagnosis and Therapymentioning
confidence: 99%
“…These observations imply that calcification of a tumor may have a positive effect on the inhibition of tumor cell proliferation, resulting in a therapeutic effect on tumors. Inspired by this, we proposed a cancer-cell-targeting calcification strategy and achieved tumor calcification spontaneously to inhibit tumor growth and metastasis induced by polycarboxylic macromolecules, , which is similar to the formation of hard tissue in living bodies, such as the physiological formation of bone and teeth. However, our pilot study implied that artificial tumor calcification showed limited tumor-inhibiting ability, as the speed of calcification is quite low, , which also impairs the ability of tumor calcification to prevent tumor metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by this, we proposed a cancer-cell-targeting calcification strategy and achieved tumor calcification spontaneously to inhibit tumor growth and metastasis induced by polycarboxylic macromolecules, , which is similar to the formation of hard tissue in living bodies, such as the physiological formation of bone and teeth. However, our pilot study implied that artificial tumor calcification showed limited tumor-inhibiting ability, as the speed of calcification is quite low, , which also impairs the ability of tumor calcification to prevent tumor metastasis. Moreover, the slow calcification process cannot induce effective tumor calcification points for medical imaging in a relatively short time, which also limits its effectiveness of tumor diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Then, the degradation of ZIF-8 and CaO 2 occurred from the exposed CaO 2 @ZIF-8/DOX in a cancer acid environment, at the same time, resulting in the release of DOX, Ca 2+ , and H 2 O 2 . The released DOX, a standard chemotherapy drug, exerted its role mainly through two ways: causing irreversible DNA damage and generating free radicals that promote oxidative stress. The produced large amounts of H 2 O 2 accumulated in the cancer cells due to the fact that catalase is downregulated, leaving cells more vulnerable to excessive stimulation of H 2 O 2 , and arrived at an oxidative stress state. As pointed out earlier, this could result in dysfunction of proteins and desensitization of calcium channels in the cell membrane followed by the accumulation of a large number of generated Ca 2+ from CaO 2 , leading to mitochondrial Ca 2+ overload-induced cell apoptosis and accompanying cancer calcification with CT signals. The TME-motivated combination therapy of mitochondrial Ca 2+ overload and anticancer drug DOX from CaO 2 @ZIF-8/DOX@HA nanosystem effectively improved the effectiveness of cancer treatments in vitro and in vivo and exhibited negligible systemic biological toxicity, indicating that the nanosystem may potentially open up a new horizon for further anticancer therapy.…”
Section: Introductionmentioning
confidence: 99%